REFLECTION OF PHILOSOPHICAL FOUNDATIONS IN FINANCIAL ACCOUNTING RESEARCH - Yeterina Widi Nugrahanti (JAFFA, 2018)
Current financial accounting research has paid little attention to the philosophical aspects that underlie the research, Hence, the existing results provide a little contribution towards the development of accounting theory and concepts. This article aims to describe the philosophical basis in financial accounting research, which consists of ontology, epistemology and axiology. The ontology and epistemology assumptions determine research paradigm, which are functionalist, interpretive and critical (radical humanist and radical structuralist). The ontology and epistemology assumptions also define the research methodology. This article outlines the taxonomy of financial accounting research formulated by Hopper and Powel (1985) and Laughlin (1995) which can be used as a guide in conducting financial accounting research. Understanding of philosophical aspects will result in high quality financial accounting research.